Pemanfaatan Big Data Dalam Penerapan Dynamic Pricing (Studi Kasus Amazon.Com) - Mar'atus Sholikhatun Nisa; Yusuf Amrozi (Jurnal SIFO Mikroskil, 2019)
Internet technology has changed human life, one of which is by using the electronic platform for business transactions or called Electronic Commerce (E-Commerce). E-Commerce company owners must implement a long-term planning method. This method has been done by Jeff Bezos by using big data to do dynamic pricing. This method has proven to be able to increase sales on Amazon. Technology customizes prices / discounts for certain items in accordance with certain customers in real-time. Buy two different customers to buy the same item from an online store with two different prices. The dynamic pricing model consists of three bottom-up layers: the data layer, the analysis layer, and the decision layer.